1998
DOI: 10.1002/(sici)1521-3773(19980316)37:5<625::aid-anie625>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Dioldehydratase Binds Coenzyme B12 in the “Base-On” Mode: ESR Investigations on Cob(II)alamin

Abstract: Even in the enzyme-bound state the dimethylbenzimidazole ligand in the dioldehydratase from Salmonella typhimurium remains bound to the cobalt ion in contrast to some coenzyme B -dependent enzymes. Direct, ESR spectroscopic proof for this "base-on" binding mode was obtained by using a coenzyme in which one of the nitrogen atoms of the dimethylbenzimidazole ligand was N labeled (see schematic representation on the right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 9 publications
3
24
0
1
Order By: Relevance
“…A possible functional advantage of the presence of a purinyl base in complete corrinoid cofactors in their H-bonding base-on constitution may therefore not be dismissed. Indeed, diol-dehydratase and cobamidedependent ribonucleotide reductase are two enzymes that depend upon adenosylcobamides and which have been discovered lately to carry their corrinoid cofactors in the base-on form (1,48,63).…”
Section: Discussionmentioning
confidence: 99%
“…A possible functional advantage of the presence of a purinyl base in complete corrinoid cofactors in their H-bonding base-on constitution may therefore not be dismissed. Indeed, diol-dehydratase and cobamidedependent ribonucleotide reductase are two enzymes that depend upon adenosylcobamides and which have been discovered lately to carry their corrinoid cofactors in the base-on form (1,48,63).…”
Section: Discussionmentioning
confidence: 99%
“…EPR studies on other AdoCbl-requiring carbon skeleton mutases reveal that these class I enzymes also utilize a histidine as their axial ligand (1,6) as do most of the cobalamin-dependent methyltransferases thus far examined (37)(38)(39). In contrast, the AdoCbl enzymes catalyzing irreversible heteroatom rearrangements, typified by DD, use the DMB moiety of the cofactor as the axial ligand (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The x-ray structures of methylmalonyl-CoA (MMCoA) mutase (3,4) and EPR studies of cob(II)alamin (2) bound to other class I enzymes (1,5,6) revealed that in each case the dimethylbenzimidazole (DMB) moiety of the cofactor is replaced by a protein-derived histidine. On the other hand, in diol dehydrase (DD), typical of the class II enzymes, DMB remains ligated to 2 (7,8). Unique among the AdoCbl-requiring enzymes is ribonucleotide reductase, the only enzyme that does not catalyze a rearrangement reaction and in which C-Co homolysis occurs concomitant with the formation of a protein-based thiyl radical (9 -11).…”
mentioning
confidence: 99%
“…This was the first crystallographic indication of the so-called 'base-on' mode of cobalamin binding to proteins, although this mode of cobalamin binding was indicated by EPR studies with 15 N-labeled coenzyme or its analogue [77,78]. In contrast, the X-ray structures of the methionine synthase cobalamin-binding domain [79], methylmalonyl-CoA mutase [74], and glutamate mutase [75], together with EPR studies on these enzymes [79][80][81], show that the DBI ligand is displaced from the cobalt atom and, instead, the imidazole group of a certain histidine residue in the cobalamin-binding motif part (DxHxxG) of proteins is ligated to the cobalt atom in these enzymes.…”
Section: Cobalamin Bindingmentioning
confidence: 99%